Disseminated Glioneuronal Tumor: A rare presentation in children - Kumari, Neha; Patil, Namrata S.; Mukherjee, Ananya; Save, Sushma U. (International Journal of Contemporary Pediatrics, 2021)
Gliomas, though most common pediatric central nervous system tumor, can manifest as disseminated glio-neuronal tumor, a rare variant in children. Clinical presentation depends on its location, type and age of child. We are presenting 8 years old male child with fever, projectile vomiting and severe headache which woke him up from deep sleep for 1 month. He had positive meningeal signs and raised intracranial tension with cerebrospinal fluid picture suggestive of partially treated meningitis. There was no improvement even on adequate duration of intravenous antibiotics and had appearance of new onset false localizing signs, MRI brain showed features of cryptococcal meningitis for which India ink staining was negative. As clinical picture was unlike of meningitis, repeat 3 tesla MRI brain was done. Expert neuro-radiologist’s opinion was in favor of disseminated glio-neuronal tumor which was confirmed on histopathological examination. Child underwent laminectomy in TATA memorial hospital and advised palliative care. Child succumbed at home within 6 months of illness.